(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The pH value of the reactor water is set for reasons of corrosion resistance of the structural materials. The lower limit of 5.8 is determined by limiting the occurrence of electrochemical corrosion with hydrogen depolarization, the upper value of 10.3 is determined by the process of alkaline embrittlement of steels and zirconium alloys.